Last Stand? The Criminal Responsibility of War Veterans Returning from Iraq and Afghanistan with Posttraumatic Stress Disorder - Hafemeister, Thomas L (2010)
As more psychologically scarred troops return from combat in Iraq and Afghanistan, society's focus on and concern for these troops and their psychological disorders has increased With this increase and with associated studies confirming the validity of the Posttraumatic Stress Disorder (PTSD) diagnosis and the genuine impact of PTSD on the behavior of war veterans, greater weight may be given to the premise that PTSD is a mental disorder that provides grounds for a mental status defense, such as insanity, a lack of mens rea, or self-defense. Although considerable impediments remain, given the current political climate, Iraq and Afghanistan War veterans are in a better position to succeed in these defenses than Vietnam War veterans were a generation ago. This Article explores the prevalence and impact of PTSD, particularly in war veterans, the relevance of this disorder to the criminal justice system, and the likely evolution of related mental status defenses as Iraq and Afghanistan War veterans return from combat